Post-indepencence stability in the Republic of South Sudan : constraints and prospects - Schoeman, Maxi (University of Pretoria, 2018)
The question of post-independence stability, its constraints and its prospects in South Sudan is explored from a variety of perspectives in this study. Central to the discussion is the view that nation and state building, together with social and political cohesion, aspects which would lead to a more stable country, are seriously lacking in the fabric of modern South Sudan. Several reasons account for this, among which the lack of leadership, the failure of political agreements and the absence of a willingness to compromise in the pursuit of national unity. The view that an understanding of the problem of stability has to be founded on a full comprehension of the political and social background to the formation of South Sudan is adopted in the study. The study proposes a holistic and comprehensive perspective through which the important subject of stability in South Sudan can be understood and possibly resolved.